Design of the Web-Based Air Conditioning Service Information System - Darmanto, Rikardus; Handayanna, Frisma; Rahayu, Sri (Informatics and Software Engineering, 2024)
PT. Marver Maju Sejahtera is a firm engaged in consulting services and AC service services. The current AC service system is ineffective when a customer comes directly to the office to request AC service, which takes quite a long time, so there is a lack of customer interest then the recording of service data still uses paper or handwritten, causing problems such as errors in recording address data or customer residence locations. In that condition, the running system can understand the constraints or problems and be able to provide the right solution. A service information system is a web-based application that makes it easy for customers and the firm to carry out activities. The system development model used is rapid application development (RAD), which is an iterative method, so the design process is carried out according to the developer's version. The result of this system is that it can process information related to AC service services, such as managing customer data, category data, service type data, report data, and service payment transaction processing.   PT. Marver Maju Sejahtera ialah perusahaan bergerak dalam bidang Jasa Konsultan dan Jasa Service AC. Sistem pelayanan jasa servis AC saat ini kurang efektif dimana seorang pelanggan datang langsung ke kantor untuk permintaan servis AC yang makan waktu cukup lama, dengan begitu kurangnya minat pelanggan, berikutnya pencatatan data servis masih menggunakan kertas atau tulis tangan sehingga menimbulkan permasalahan seperti kesalahan pencatatan data alamat atau lokasi tinggal pelanggan. Untuk sistem yang berlangsung agar dapat memahami kendala atau permasalahan dan dapat memberikan solusi yang tepat. Sistem informasi jasa servis AC merupakan suatu aplikasi berbasis web, yang memberikan kemudahan untuk pelanggan dan pihak perusahaan dalam melakukan kegiatan. Model sistem pengembang yang digunakan Rapid Application Development (RAD) yang Merupakan salah satu metode berulang, sehingga proses desain dilakukan sesuai versi developer. Hasil sistem ini ialah bisa memproses informasi berkaitan dengan jasa servis AC, seperti: mengelola data pelanggan, data kategori, data jenis jasa, data laporan, proses transaksi pembayaran servis.